PENGARUH TINGKAT PENDIDIKAN, KECERDASAN SPIRITUAL DAN TINGKAT PENGHASILAN TERHADAP PERSEPSI ETIS SISWA AKUNTANSI TERHADAP PROFESI AKUNTANSI (Studi pada Mahasiswa Akuntansi Institut Agama Islam Negeri Parepare) - Amalia (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2024)
The accounting profession holds a vital role in managing a company's finances, bearing substantial responsibility for overseeing financial flows and ensuring the accuracy of transactions. Nevertheless, the growing occurrence of accounting misconduct, such as the manipulation of financial reports, has eroded public trust in this profession. This research aims to explore several factors influencing accounting students' ethical perceptions of the profession. Specifically, it investigates the impact of education level, spiritual intelligence, and income level on these ethical perceptions. Furthermore, the study examines the combined effect of education level, spiritual intelligence, and income level on the ethical views of accounting students regarding their profession. A quantitative approach was adopted in this research, utilizing field research methods, particularly a questionnaire survey. To analyze the data, several testing techniques were employed, including descriptive statistics, validity and reliability tests, normality, multicollinearity, heteroscedasticity, multiple linear regression, the coefficient of determination (R²), F statistical tests, and t statistical tests. The findings indicate that education level positively and significantly affects the ethical perceptions of accounting students toward the accounting profession. Similarly, spiritual intelligence also has a positive and significant influence. However, income level does not significantly impact the ethical perceptions of accounting students. When examined collectively, education level, spiritual intelligence, and income level together significantly influence the ethical views of accounting students regarding their profession.